PENINGKATAN LAJU DISOLUSI FENOFIBRAT MELALUI PEMBENTUKAN KOMPLEKS INKLUSI MENGGUNAKAN F3 SIKLODEKSTRIN DAN HIDROKSIPROPIL 13 SIKLODEKSTRIN - Febi Akbari, Okta
Fenofibrate is a drug compound which is practically insoluble in water, has poor dissolution rate and low bioavailability. One of the methods to increase dissolution rate and solubility of substance in water is by formation of inclusion complex. The aim of this research is to increase dissolution rate of fenofibrate by preparation of inclusion complex of fenofibrate with I3-cyclodextrin (BCD) and its derivate hydroxypropil-P-cyclodextrin HPBCD). Inclusion complex of fenofibrate with BCD or HPBCD are made by solubilizstion method with mol ratio of 1:1 2:3 and 1:2. Evaluation of inclusion complex consists of dissolution tests, solubility, infrared spectrophotometry and Scanning Electron Microscopy (SEM). Then the inclusion complexes which possessed highest dissolution rate were formulated into tablet, and the dissolution of fenofibrate from tablet is tested.The solubility of fenofibrate was increased with formation of inclusion complex. The highest dissolution rate of fenofibrate from each of inclusion complex are shown by inclusion complex of fenofibrate-BCD with mol ratio 1:2, and inclusion complex with 1-IPBCD 1:1 which were 68.93 + 1.21% and 76.06% ± 3.31% respectively after 60 minutes. Characterization of inclusion complex with infrared spectrophotometry showed that there was no interaction occured between fenofibrate with BCD or HPBCD and the microphotograph obtained from SEM showed that there were still a lot of fenofibrate crystal that were not form an inclusion complex outside of BCD or HPBCD particle. The dissolution of fenofibrate from it inclusion complex after compressed into tablet was influenced by it formulation. Tablet that showed the highest dissolution rate was tablet that contained an inclusion complex of Fenofibrate-BCD 1:2 which was 64.38% 2.26%. From one way ANOVA test we can conclude that the dissolution rate of fenofibrate from powder or tablet of inclusion complexes using solubilization method have significant differences with it physical mixture, and pure fenofibrate.